Kecukupan Konsumsi Pangan Hewani di Kota Jambi dalam Hubungannya Kualitas Sumberdaya Manusia Keluarga Serta Faktor-Faktor Yang Mempengaruhinya - Farhan, Muhammad (Fakultas Peternakan Universitas Jambi, 2008)
This research was aimed to 1) determine the sufficiency of animal food consumption such as amount of food consumption, animal protein and energi consumption for the healthy life, 2) find the correlation between sufficincy of animal food consumptionand human resources quality and, 3) determine family member appetite on animal food consumption, food accessibility, income per capita, 4) find the correlation between animal food availability in their house hold to the sufficiency of animal food consumption . the research was condcted by survey in 2 steps namely discriptive and representative steps. Sample were collected by multi stage cluster random sampling and sample size were fixed by iteratif methode . Correlation and patway abalysis were used as analysis model. This study concluded that ; 1) Animal food consumption in Jambi regency was still under animal food consumption standard, 2) More sufficient animal food consumption did not inprove quality of human resorces of family member, 3) Sosisal culture and economic condition of the family and animal food availability at the house hold level had significant food consumption, animal protein and energy